2011
DOI: 10.3174/ajnr.a2734
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MR Imaging of the Temporomandibular Joint Using a Balanced Steady-State Free Precession Sequence at 3T

Abstract: SUMMARY:The aim of our project was to develop an MR imaging protocol for dynamic imaging of the TMJ. We imaged a total of 24 joints in 12 subjects. We developed an imaging protocol on a 3T system using the true FISP sequence that yielded an acceptable spatial and temporal resolution for dynamic MR imaging.ABBREVIATIONS bSSFP ϭ balanced steady-state free precession; FISP ϭ fast imaging with steady-state precession; HASTE ϭ half-Fourier acquired single-shot

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The bSSFP sequences use an ultrashort TR (typically in the range of 3–6 ms, allowing for fast k-space acquisition with sufficiently large matrix sizes, e.g., 128 or 256 in each dimension). Due to use of alternating polarity RF pulses, bSSFP sequences have large steady-state magnetization, which provides a high SNR [19]. In the present study, we found that wrist images can be acquired rapidly (<35 s) during motion in a reliable manner using a bSSFP pulse sequence, particularly when artifacts are minimized by the use of dielectric pads.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The bSSFP sequences use an ultrashort TR (typically in the range of 3–6 ms, allowing for fast k-space acquisition with sufficiently large matrix sizes, e.g., 128 or 256 in each dimension). Due to use of alternating polarity RF pulses, bSSFP sequences have large steady-state magnetization, which provides a high SNR [19]. In the present study, we found that wrist images can be acquired rapidly (<35 s) during motion in a reliable manner using a bSSFP pulse sequence, particularly when artifacts are minimized by the use of dielectric pads.…”
Section: Discussionmentioning
confidence: 54%
“…In a single-slice sequential acquisition mode, bSSFP has been applied successfully to dynamic imaging of the actively moving temporomandibular joint [19], but not to study static and dynamic instability in the wrist. There has been concern that bSSFP may not be technically feasible in the moving wrist because relatively small magnetic field inhomogeneities can generate substantial banding artifacts [18].…”
Section: Introductionmentioning
confidence: 99%
“…MR evaluation of the TMJ is useful to detect alterations in disc morphology or position, joint effusion and some of the signs related with osteoarthritis (OA) [2,7,8]. Furthermore, dynamic and pseudo-dynamic studies of the TMJ can be obtained with MRI as the patient opens and closes the mouth [911]. …”
Section: Introductionmentioning
confidence: 99%
“…Second, previous studies assume the tumor position detection at 30 Hz by monitoring the position of external or internal tumor surrogates using optical tracking devices, 15,16 or a stereoscopic x-ray fluoroscopy system. 12,13 However, dynamic MR imaging to observe organ motion of lung, 7 intrathoracic tumor, 19 joint, 20 etc., can typically achieve imageacquisition rates of 3-4 frames per second (fps). This rate is recommended for real-time tracking of lung-tumor motion 21 and can be achieved using our present linac-MR.…”
Section: Introductionmentioning
confidence: 99%